Don't ditch the women - poster, 1968 (1968)
1968 1960-2000 "Don't ditch the women - poster, 1968" [EP0022], 1968 Lobby outside Congress House, the TUC headquarters building, on 22 November 1968. The recall conference of the Amalgamated Union of Engineering and Foundry Workers, meeting inside the building, took place following the suspension of a national strike across the engineering industry in support of a claim which had included a call for progress towards equal pay. The recall conference agreed to accept the employers' wage proposals, which had the effect of widening the gap between men's and women's basic rates, and agreed instead to enter job evaluation discussions on women's wages.